A flow cytometry‐based method for a high‐throughput analysis of drug‐stabilized topoisomerase II cleavage complexes in human cells. Issue 9 (12th August 2016) - de Campos‐Nebel, Marcelo; Palmitelli, Micaela; González‐Cid, Marcela
Abstract: Topoisomerase II (Top2) is an important target for anticancer therapy. A variety of drugs that poison Top2, including several epipodophyllotoxins, anthracyclines, and anthracenediones, are widely used in the clinic for both hematologic and solid tumors. The poisoning of Top2 involves the formation of a reaction intermediate Top2‐DNA, termed Top2 cleavage complex (Top2cc), which is persistent in the presence of the drug and involves a 5′ end of DNA covalently bound to a tyrosine from the enzyme through a phosphodiester group. Drug‐induced Top2cc leads to Top2 linked‐DNA breaks which are the major responsible for their cytotoxicity. While biochemical detection is very laborious, quantification of drug‐induced Top2cc by immunofluorescence‐based microscopy techniques is time consuming and requires extensive image segmentation for the analysis of a small population of cells. Here, we developed a flow cytometry‐based method for the analysis of drug‐induced Top2cc. This method allows a rapid analysis of a high number of cells in their cell cycle phase context. Moreover, it can be applied to almost any human cell type, including clinical samples. The methodology is useful for a high‐throughput analysis of drugs that poison Top2, allowing not just the discrimination of the Top2 isoform that is targeted but also to track its removal. © 2016 International Society for Advancement of Cytometry